Identification of Landslide Hazard in Residential Area Kubang Tangah District, Sawahlunto - Andriani Andriani; Bambang Istijono; Alfito Alfito; Farid Akmal; Bayu Martanto Adji (Journal of Applied Engineering and Technological Science (JAETS), 2024)
The residential area in Kubang Tangah, Sawahlunto, is an area that has the potential for significant landslide hazard. With rapid residential growth and environmental change, risks to the security and well-being of residents are becoming increasingly prominent. This research aims to identify factors that trigger landslide hazard and analyze potential risks in the residential context of Kubang Tangah. Analysis of regional geotechnical and topographic characteristics, land use modeling, and review of the impact of human activities on slope stability. The analysis method uses the Plaxis 2D program to obtain slope safety factors in the Kubang Tangah residential area, Sawahlunto. The research results show that residential areas in Kubang Tangah have a high level of landslide risk, influenced by slope, soil type, and changes in land use. Varying rainfall levels significantly contribute to the potential for landslide hazard. Mitigation recommendations are suggested to involve wise land use changes, strengthening infrastructure, and increasing public awareness of the dangers of landslides.